Stenting the Ductus Arteriosus of a Patient with Tetralogy of Fallot and Trisomy 18: Case Report and Updated Review - Sá Filho, Márcio Erlei Vieira de; Delgado, Marina Ayres; Branco, Bruno Vinicius Castello; Nascimento, David Ribeiro do (Brazilian Journal of Case Reports, 2025)
Ductal stent implantation is a palliative procedure that can be performed in cases of congenital heart defects dependent on the patency of the ductus arteriosus, such as Tetralogy of Fallot. It is a widely effective technique, with low complication rates and less invasive than the modified Blalock-Taussig palliative surgery, making it a viable and safe option for high-surgical-risk patients. Moreover, it is crucial for the anesthesiologist to be familiar with the pathophysiological characteristics of these ductus arteriosus-dependent heart conditions to ensure appropriate perioperative management. The objective of this work is to describe the challenging anesthetic management of a newborn with Tetralogy of Fallot and Edwards Syndrome who underwent ductal stent implantation via endovascular approach at a quaternary care center.